Phylogeny and fatty acid profiles of new Coccomyxa (Chlorophyta) species from soils of Vietnam - Maltsev, Yevhen; Kezlya, Elena; Maltseva, Svetlana; Krivova, Zinaida; Ðinh, Cù Nguyên; Kulikovskiy, Maxim (Frontiers in Microbiology, 2025)
IntroductionA new algal species of Coccomyxa, C. cattiensis sp. nov., C. fusiformis sp. nov., and C. tropica sp. nov. are recorded in the tropical forest soil from the Cát Tiên National Park, Vietnam.MethodsThe analysis is based on morphological characters, evolutionary distance, 18S rDNA phylogeny, and ITS2 secondary structure.ResultsNew species differed from other species of the genus by the size and shape of vegetative cells, and habitat type. The evolutionary distance matrix based on the 18S rRNA gene shared 97.9–100% similarities with other Coccomyxa sequences. The phylogeny inferred by maximum likelihood and Bayesian inference placed new species in the independent lineages close to clades C. subellipsoidea, C. polymorpha, and C. parasitica. Predicted secondary structures of the ITS2 of new species differed from the Coccomyxa species by compensatory base changes, deletions, and single bases. Fatty acid composition analysis was performed on Coccomyxa strains from tropical habitats for the first time. α-linolenic (26.8–47.0%), palmitic (13.6–31.2%), and linoleic (up to 21.7%) acids were the dominant fatty acids in the algae cultured on the BBM medium.ConclusionHigh concentrations of omega-3 polyunsaturated fatty acids (up to 485 mg L–1) position the novel Coccomyxa strains as a promising feedstock for the food and pharmaceutical, agricultural, and aquaculture industries.